Waste lithium battery graphite purification, repair and regeneration method, graphite negative pole piece and lithium battery
By combining the method of high-frequency alternating magnetic field and plasma coupling field, efficient peeling and deep purification of graphite of waste lithium batteries is achieved, and the problems of high energy consumption and pollution in the existing technology are solved, and the electrochemical performance standards of commercial lithium-ion batteries are met.
Patent Information
- Application Number
- CN202510352046.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
In the recycling and regeneration of waste lithium batteries, the existing technology has problems such as high temperature, high energy consumption, serious pollution, and the impurity content after graphite purification cannot meet industrial standards.
The method of combining high-frequency alternating magnetic field and plasma coupling field is adopted to quickly heat up and form a temperature gradient through the eddy current effect of the copper current collector, and the graphite is peeled off with ultrasonic vibration. Then, the amorphous carbon, metals and oxides in the graphite are removed through dilute acid solution dispersion, reverse flotation, EDTA chelation and oxidation purification, and finally the graphite structure is repaired by high-temperature carbonized asphalt coating.
It achieves efficient peeling and deep purification of graphite, reduces energy consumption and pollution, and the purified graphite has a complete structure, low content of impurities, and its electrochemical performance reaches the standards of commercial lithium-ion batteries.
Smart Images

Figure CN119864534A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of recycling and regenerating waste lithium batteries, and specifically relates to a method for purifying, repairing and regenerating graphite of waste lithium batteries, a graphite negative electrode sheet and a lithium-ion battery. Background Art
[0002] After 5 to 8 years of use, the capacity of lithium batteries will decay to a certain extent, resulting in a large amount of waste. Waste lithium batteries contain 35 to 45 wt% lithium metal oxide, 15 to 25 wt% graphite, 10 to 20 wt% carbonate electrolyte, 2 to 5 wt% polypropylene separator and 15 to 30 wt% metal material.
[0003] Compared with the metal in the battery, the utilization value of waste graphite is lower. In the industrial recycling process, lithium resources are mainly recovered from waste graphite. The carbon slag after lithium extraction is generally used as a recarburizer or reducing agent in the smelting industry. However, graphite is a non-renewable resource and has an important strategic position. In the production process of negative electrode materials, the energy consumption of graphitization processing is high, accounting for about half of the production cost of negative electrode materials. The recycled waste graphite still maintains an ordered structure and does not need to be treated at high temperature again, thereby reducing costs. In addition, compared with graphite ore, the graphite content in waste batteries is higher and the types of impurities are less, so that its recycling can shorten the process flow and reduce energy loss. Therefore, in the resource utilization of waste lithium batteries, it is of great significance to recover and repair the failed negative electrode graphite, which can realize the recycling of resources and is conducive to protecting the environment and developing the economy.
[0004] Waste lithium batteries can be recycled to obtain failed negative electrode sheets through constant potential discharge pretreatment and refined disassembly. Among them, graphite and conductive carbon black are tightly adhered to the copper foil current collector through a binder to form a negative electrode. The multiphase interface dissociation of this structure is the key to the stripping of active substances. Oily binders (such as PVDF) have the characteristics of high bonding strength, high chemical stability and better compatibility with electrolytes, and have been widely used as negative electrode binders in lithium batteries. At present, liquid phase dissolution and high temperature pyrolysis methods are often used to strip negative electrode sheets at home and abroad. Among them, the stripping of graphite and copper foil can be achieved by washing and dispersing the aqueous binder, or by swelling the oily binder with an organic solvent, and supplemented by ultrasonic vibration. However, in the large-scale stripping process, the complex binder system limits the application of the above-mentioned single liquid phase stripping method. In addition, the pole pieces obtained after disassembling the lithium battery often contain organic matter such as SEI film and carbonate electrolyte, which will pollute the water body during the liquid phase stripping process. High-temperature pyrolysis is the most direct and effective stripping method. It removes conductive additives and organic binders by decomposition, reduces the cohesion of coating material particles, and weakens the adhesion between the coating and the current collector. However, the temperature of pyrolysis and debonding of the binder is high (>500°C), which can easily cause partial graphite carbon loss, high energy consumption, and fluorine-containing waste gas pollution of the environment. In addition, this method requires inert atmosphere protection to avoid oxidation and combustion of graphite and oxidation and brittleness of copper foil at high temperatures.
[0005] The failed graphite powder obtained by stripping off the copper foil current collector usually retains impurities such as amorphous carbon, SEI film, metal particles and residual electrolyte organic matter, which seriously affect the electrochemical performance. Methods for graphite impurity removal and purification include flotation, screening, chemical acid leaching and alkali treatment, and high-temperature calcination. Among them, the air flow flotation method can effectively separate amorphous carbon and graphite, but the accuracy is poor and the efficiency is low; the high-temperature calcination method (>2500℃) can decompose various impurities, but the energy consumption is high; the gradient calcination method and hydrochloric acid leaching method can leach out metal impurities such as lithium ions, but there is secondary pollution of harmful gases such as chlorine and equipment corrosion, and there are problems such as low organic matter removal efficiency and high pollution in the impurity treatment process. The impurity content after purification is still difficult to meet the standards of "Graphite Anode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0006] Failed graphite often has microstructural damage, which manifests as surface oxidation and internal holes. In addition, the recycled graphite is also prone to microscopic defects and hard carbon impurities after low-temperature roasting and wet purification. Surface coating is also a method for repairing and regenerating waste graphite. The coating material can improve the defects on the graphite surface. The coating layer forms a continuous conductive network on the graphite surface, which can improve the transmission of electrons and increase the conductivity. Usually, the waste graphite is pretreated to remove impurities, and then glucose, asphalt, phenolic resin, metal base and other materials are coated on the pretreated graphite, but there are problems such as uneven coating and low vibration and compaction density. Summary of the invention
[0007] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art and to provide a method for purifying, repairing and regenerating graphite from waste lithium batteries, as well as a graphite negative electrode sheet and a lithium-ion battery prepared using the regenerated graphite obtained by the method as an active material.
[0008] In a first aspect, the present application provides a method for purifying, repairing and regenerating graphite from waste lithium batteries, comprising the following steps: S1. Placing the negative electrode of the waste lithium battery in a high-frequency alternating magnetic field, controlling the electromagnetic induction heating current to be within the range of 200A to 500A, the alternating magnetic field frequency to be 20 to 30kHz, the surface temperature of the copper current collector in the negative electrode of the waste lithium battery to be 350 to 400°C, and treating the negative electrode of the waste lithium battery with a plasma generator, the pulse power of the plasma generator to be 20 to 50kW, so that cracks are formed in the coating between the graphite in the negative electrode of the waste lithium battery and the copper current collector and the interface between the coating and the copper current collector is dislocated, and then the graphite is peeled off from the copper current collector by ultrasonic vibration, and the graphite particles are recovered after sieving; S2. dispersing the recovered graphite particles in a dilute acid solution, adding a graphite flotation inhibitor, stirring, adding an amorphous carbon capture agent, stirring, and then adding a frother, and after reverse flotation, removing the amorphous carbon; S3: mixing the product obtained in step S2 with a dilute acid solution, then adding a chelating agent, stirring to form a chelate, and then washing with a dilute acid solution to leach out metals, oxides and inorganic substances in the SEI film in the product, thereby obtaining a preliminarily impurity-removed graphite substrate; S4: adjusting the pH value of the preliminarily impurity-removed graphite substrate obtained in step S3 to 2-3, adding ferrous sulfate heptahydrate, adding hydrogen peroxide dropwise after sufficient stirring, and then stirring to react to oxidize and decompose organic matter in the SEI film and the carbonate electrolyte remaining on the surface of the graphite particles, and filtering, washing, and drying to obtain deeply purified graphite; S5: adding high-temperature petroleum asphalt to the deeply purified graphite obtained in step S4, kneading through a screw kneading device and then carbonizing at high temperature to obtain regenerated graphite with repaired structure and carbon coating on the surface.
[0009] In a second aspect, the present application also provides a graphite negative electrode plate, which is prepared using the regenerated graphite obtained by the above method as the negative electrode active material.
[0010] In a third aspect, the present application also provides a lithium-ion battery, comprising the above-mentioned graphite negative electrode sheet.
[0011] The present application provides a method for purifying, repairing and regenerating graphite of waste lithium batteries. The negative pole piece of the waste lithium battery is placed in a high-frequency alternating magnetic field and an atmospheric plasma coupling field. The temperature is rapidly raised by the eddy current effect of the copper collector to form a temperature gradient with the graphite coating. The organic matter of the pole piece is cleaned by a high-energy jet of air plasma simultaneously. The binder is pyrolyzed by controlling the temperature. The ultrasonic vibration realizes efficient peeling of the graphite particles. Then, the recovered graphite particles are subjected to coordinated treatment of shear homogenization dispersion, reverse flotation, EDTA chelation and oxidation purification. Impurities such as amorphous carbon, metals and oxides, SEI film and organic matter in the graphite particles can be effectively removed, thereby realizing deep purification of the graphite. The deeply purified graphite is first degassed at low pressure in a room temperature section by a segmented and integrated screw. Then, the micro-liquefied asphalt and the deeply purified graphite are kneaded and extruded to fill the internal pores and surface of the deeply purified graphite in a medium temperature section. Finally, the graphite is carbonized in a high temperature section so that the carbonized asphalt is mixed and melted with the graphite to realize the repair and regeneration of the graphite structure. The graphite negative electrode material for lithium-ion batteries (GB / T 24533-2019) standards (fixed carbon content > 99.7%, iron < 100ppm, copper < 5ppm, aluminum < 5ppm, magnetic foreign matter < 0.5ppm, first-cycle coulomb efficiency in electrochemical performance ≥ 91.0%), which meets the application requirements of commercial lithium-ion battery graphite negative electrode materials.
[0012] The method for purifying, repairing and regenerating graphite from waste lithium batteries in the present application realizes the secondary utilization of recycled negative electrode graphite from waste lithium-ion batteries, solves the problem of recycling and processing waste lithium-ion batteries, realizes the resource conversion of waste lithium-ion batteries, and can ensure the quality of recycled negative electrode graphite.
[0013] The present application uses graphite recovered from waste lithium-ion batteries as raw material, and prepares graphite negative electrode sheets and lithium-ion batteries after purification, repair and regeneration. This can not only recycle resources, but also reduce the manufacturing cost of lithium-ion batteries, and realize efficient and high value-added resource recycling of waste lithium-ion batteries, with significant industrial application prospects and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a process flow chart of the method for purifying, repairing and regenerating graphite from waste lithium batteries of the present application;
[0015] Figure 2 The XRD spectrum of the graphite obtained by the methods for purifying and repairing waste lithium battery graphite in Examples 1 to 3 of the present application and the methods in Comparative Examples 1 to 4;
[0016] Figure 3 This is a SEM picture of graphite obtained by the method of Example 1 of the present application;
[0017] Figure 4 This is the voltage-specific capacity curve of the first cycle of graphite charge and discharge obtained by the method of Example 1 of the present application;
[0018] Figure 5 This is a SEM picture of graphite obtained by the method of Example 2 of the present application;
[0019] Figure 6 This is the voltage-specific capacity curve of the first cycle of graphite charge and discharge obtained by the method of Example 2 of the present application;
[0020] Figure 7 This is a SEM picture of graphite obtained by the method of Example 3 of the present application;
[0021] Figure 8 This is the voltage-specific capacity curve of the first cycle of graphite charge and discharge obtained by the method of Example 3 of the present application;
[0022] Fig. 9 This is a SEM picture of graphite obtained by the method of Comparative Example 1;
[0023] Fig.10 The voltage-specific capacity curve of the first cycle charge and discharge of graphite obtained by the method of comparative example 1;
[0024] Fig.11 This is a SEM picture of graphite obtained by the method of Comparative Example 2;
[0025] Fig.12 The voltage-specific capacity curve of the first cycle charge and discharge of graphite obtained by the method of comparative example 2;
[0026] Fig.13 This is a SEM picture of graphite obtained by the method of Comparative Example 3;
[0027] Fig.14 The voltage-specific capacity curve of the first cycle charge and discharge of graphite obtained by the method of comparative example 3;
[0028] Fig.15 This is a SEM picture of graphite obtained by the method of Comparative Example 2;
[0029] Fig.16 The voltage-specific capacity curve of the first cycle charge and discharge of graphite obtained by the method of comparative example 2;
[0030] Fig.17 are the physical and chemical performance parameters of graphite obtained by the methods of Examples 1 to 3 of the present application;
[0031] Fig.18 These are the physical and chemical performance parameters of the graphite obtained by the methods of Comparative Examples 1 to 4 of the present application. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0033] See also Figure 1 The present application provides a method for purifying, repairing and regenerating graphite from waste lithium batteries, comprising the following steps:
[0034] S1 places the negative electrode of the waste lithium battery in a high-frequency alternating magnetic field, controls the electromagnetic induction heating current to be within the range of 200A to 500A, the alternating magnetic field frequency to be between 20 and 30kHz, and the surface temperature of the current collector in the negative electrode of the waste lithium battery is 350 to 400°C. At the same time, a plasma generator is used to treat the negative electrode of the waste lithium battery, and the pulse power of the plasma generator is controlled to be between 20 and 50kW, so that cracks are formed in the coating (adhesive) between the graphite in the negative electrode of the waste lithium battery and the current collector, and the interface between the coating and the current collector is dislocated, and then the graphite is peeled off from the current collector by ultrasonic vibration, and the sieved material is taken after sieving to obtain recycled graphite particles.
[0035] The air flow rate in the high-frequency alternating magnetic field of this step is controlled at 10-20 L / min, the processing time of the whole step is 30-60 s, and the mesh number of the ultrasonic vibration screen is 150-300 meshes.
[0036] In this step, after the waste lithium battery is discharged at a constant potential, the negative electrode pieces are disassembled, crushed and sorted, and then the recovered negative electrode pieces are placed in a high-frequency alternating magnetic field and plasma environment for treatment, and the working parameters of the electromagnetic induction and plasma generator are controlled. The surface of the waste negative electrode pieces is cleaned by low-temperature atmospheric plasma, and the air flow in the high-frequency alternating magnetic field is controlled at 10-20L / min. The active oxygen in the air is used to make the surface temperature of the collector in the negative electrode piece of the waste lithium battery between 350 and 400°C, so that the surface of the negative electrode piece is accelerated to be bombarded at a lower temperature (<400°C). It can partially decompose the binder and organic matter attached to the graphite coating in a very short time (<60s), retain part of the binder, reduce the amount of flotation inhibitor needed to be added in subsequent steps, and form large cracks in the coating between the graphite and the current collector, which helps to improve the subsequent ultrasonic vibration de-powdering rate (>92%). It also solves the problems of high-purity inert gas protection (>99.99%), high-temperature complete reaction (>550℃) and long-term full oxidation (>1h) during the traditional negative electrode sheet stripping, which can reduce the cost of negative electrode sheet stripping.
[0037] At the same time, this step adopts high-frequency alternating magnetic field induction heating of the negative electrode plate, and uses the eddy current effect of the current collector to quickly heat up (>200℃ / s), so that the instantaneous differential temperature (temperature gradient) of the current collector (active heating by eddy current) and the graphite coating (passive heating by heat conduction) forms thermal stress, and the interfacial shear force caused by the differential thermal expansion volume change of the metal (current collector) and graphite forms a dislocation at the interface between the current collector and the graphite coating, which can further improve the subsequent ultrasonic vibration powder removal and stripping rate (>96%), solving the low efficiency (<10℃ / s) problem of the prior art in the heating stage of heating by heat conduction or thermal radiation through resistance wire.
[0038] This step uses high-frequency alternating magnetic field and atmospheric plasma coupling, which are used in synergy. While partially cracking the binder and organic matter attached to the graphite, dislocations are formed at the interface between the coating and the current collector, which provides conditions for the subsequent ultrasonic vibration of the graphite powder to peel off the current collector, and can obtain a higher peeling rate (>99%). Moreover, in this process, only part of the organic impurities in the negative electrode are oxidized, and the removal of the remaining organic matter is centralized during the subsequent liquid phase purification, which improves the environmental friendliness of the treatment process. Furthermore, the metal eddy current is used to quickly heat up and the high-pressure plasma gas flow is accelerated. Its energy consumption is about 1 / 10 of other physical heating methods, and the time is about 1 / 60 of other high-temperature pyrolysis, which greatly reduces energy consumption, saves energy, and solves the problem of the compatibility of a single method for complex systems of different binders (such as water-based CMC, SBR, PAA and oily PVDF).
[0039] This step does not require inert atmosphere treatment, and has a short treatment time and low energy consumption.
[0040] S2 Disperse the recovered graphite particles in a dilute acid solution, then add a graphite flotation inhibitor, stir and add an amorphous carbon capture agent, stir and add a frother, and remove the amorphous carbon after reverse flotation for 10 to 15 minutes.
[0041] In a preferred embodiment of this step, when the graphite particles are dispersed in a dilute acid solution, the solid-liquid ratio of the graphite particles to the dilute acid solution is 10 to 50 g / L, the dilute acid may preferably be sulfuric acid, and the concentration of the sulfuric acid solution is 0.05 to 0.10 mol / L; the graphite flotation depressant is selected from at least one of sodium carboxymethyl cellulose or water glass, the solid-liquid ratio of the graphite particles to the graphite flotation depressant is 0.3 to 1 g / L, and the graphite flotation depressant is added and stirred for 10 to 20 minutes; the amorphous carbon capture agent is selected from at least one of sodium dodecylbenzene sulfonate or oleic acid, the solid-liquid ratio of the graphite particles to the amorphous carbon capture agent is 0.1 to 0.2 g / L, and the amorphous carbon capture agent is added and stirred for 10 to 20 minutes; the foaming agent is selected from at least one of methyl isobutyl carbinol or 2-ethylhexanol, and the solid-liquid ratio of the graphite particles to the foaming agent is 0.05 to 0.15 g / L.
[0042] In a preferred embodiment of the present application, the recovered graphite particles are dispersed in a dilute acid solution in a stator-rotor high shear homogenizer, with a shear speed of 9000 to 12000 rpm and a time of 60 to 120 min.
[0043] This step uses a stator and rotor high shear homogeneous dispersion and stripping of the negative electrode material, using a higher linear speed and a smaller gap between the stator and rotor, and through strong turbulence, shear separation of amorphous carbon impurities (including conductive carbon black and high-temperature pyrolysis amorphous carbon, etc.) and graphite, which helps to enhance the dispersion of graphite in the aqueous phase and the leaching of water-soluble impurities, and solves the problems of difficult wetting of the surface of powder particles and difficult breakup of agglomerate particles in traditional dispersion methods, and can improve the recovery rate and recovery quality of graphite.
[0044] In the field of recycling and separation of waste ion battery materials, flotation methods are usually used to change the hydrophilicity and hydrophobicity of positive electrode active materials and negative electrode graphite, and separation needs to be achieved by adding a large amount of reagents. The present application uses reverse flotation to separate graphite and amorphous carbon. Under the action of a frother, a graphite flotation inhibitor is used to keep the graphite hydrophilic, so that it is dispersed in the solution or sinks to form a substrate. At the same time, an amorphous carbon capture agent is used to float the amorphous carbon to improve the sorting accuracy. Due to the low content of amorphous carbon (<5wt%), the amount of capture agent and frother used is lower than that of traditional methods. In addition, the CMC and its derivatives remaining in the recovered exfoliated graphite can still promote the dispersion of graphite in water, so the amount of flotation inhibitor used is relatively low. In this way, the use of external reagents can be reduced and the quality of graphite recovery can be improved.
[0045] S3: Mix the product obtained in step S2 with a dilute acid solution, then add a chelating agent, stir to form a chelate, and then wash with a dilute acid solution to leach out metals, oxides in the product and inorganic substances in the SEI film to obtain a preliminarily decontaminated graphite substrate.
[0046] The diluted acid in this step is also preferably sulfuric acid, and the concentration of the sulfuric acid solution is 0.05-0.10 mol / L. The solid-liquid ratio of the product obtained in step S2 to the sulfuric acid solution is 10-50 g / L. The chelating agent is ethylenediaminetetraacetic acid (EDTA), and the mass ratio of graphite particles to ethylenediaminetetraacetic acid is 1:0.01-0.05. The stirring time after adding the chelating agent ethylenediaminetetraacetic acid is 10-20 min.
[0047] In this step, the metal oxides in the recovered graphite particles undergo double decomposition reaction under the action of acid to generate soluble metal salts. The double decomposition reaction precipitates metal impurity elements, which are further treated by EDTA chelation. EDTA forms chelates with metal ions, and then centrifugal sedimentation is performed to remove the metal impurity components in the graphite particles. The graphite particles are then washed with a dilute acid solution to elute and separate the trace metal ions remaining in the graphite, and the impurities are further purified. In this way, the leaching efficiency of metal ions in the graphite particles can be greater than 99% at room temperature (~25°C), and inorganic substances in oxides and SEI films can be removed, thereby solving the high energy consumption problem of heating (>80°C) required for conventional wet leaching of graphite.
[0048] S4: The pH value of the preliminarily impurity-removed graphite substrate obtained in step S3 is adjusted to 2-3, ferrous sulfate heptahydrate is added, hydrogen peroxide is added dropwise after sufficient stirring, and the reaction is stirred again to further purify the preliminarily impurity-removed graphite substrate to oxidatively decompose organic matter in the SEI film and carbonate electrolyte remaining on the surface of graphite particles, and deep purified graphite is obtained after filtering, deionized water washing, heating and drying.
[0049] In this step, ferrous sulfate heptahydrate was added at 140-560 mg / L, stirred for 10-20 min, and then hydrogen peroxide was added dropwise at 85-340 mg / L in batches at a dropping speed of 2-5 mL / min·m 3 , and further stirred for 30 to 60 minutes, the molar ratio between hydrogen peroxide and ferrous ion is 1:1 to 5:1.
[0050] This step is an oxidation purification process for the preliminarily impurity-removed graphite substrate. Ferrous sulfate heptahydrate combined with hydrogen peroxide produces highly active hydroxyl radicals in an acidic environment (pH 2-3), which can completely oxidize residual carbonate organic matter, organic impurities in the SEI film, residual amorphous carbon, and other added organic agents at room temperature to remove organic matter generated during the purification of graphite. The above process is a centralized treatment of organic impurities, which removes organic impurities in graphite, improves the degree of graphite purification, and is fully compatible with the differentiated treatment of different recycled pole sheet components.
[0051] S5: adding high-temperature petroleum asphalt to the deeply purified graphite obtained in step S4, kneading through a screw kneading device and then carbonizing at high temperature to obtain regenerated graphite with repaired structure and surface carbon coating.
[0052] This step is divided into three parts:
[0053] The first stage: first put the deeply purified graphite into the screw kneading equipment, control the screw extrusion pressure between 0.01 and 0.05 MPa, and degas at room temperature for 2 to 5 minutes, and use the low pressure stage to discharge the gas on the surface and pores of the deeply purified graphite.
[0054] The second stage: add 2.5-8wt% of asphalt to the deep purified graphite, and knead the deep purified graphite and asphalt at a temperature higher than the softening point of solid asphalt. The softening point of solid asphalt is 220-280℃. Heat for 15-25min to make the solid asphalt slightly liquefied. The screw extrusion pressure of the screw kneading equipment is 0.20-0.30MPa, and the kneading time is 5-10min. The high-pressure end of the screw kneading equipment is used to extrude and fill the micro-liquefied asphalt mixed in the deep purified graphite into the internal pores and surface of the deep purified graphite, so that the carbonized asphalt is mixed and melted into one, so as to reduce micro defects and improve the degree of graphitization (>97.0%). Moreover, this high-pressure extrusion also improves the vibration effect between the deep purified graphite and the asphalt (>1.1g / cm 3 ) and compacted density (>1.9g / cm 3 ) as well as the uniformity and efficiency of graphite coating, and can make the carbon material completely embedded in the internal pores of graphite, solving the problems of difficult wetting and difficult penetration of internal pores of traditional asphalt-coated graphite.
[0055] In addition, this step uses a screw kneading device. Its segmented, integrated screw can efficiently mix and achieve continuous feeding through continuous mixing - micro-liquefied flow pressure infiltration of asphalt to fill the internal pores and coat the graphite, solving the problem of pre-burning and segmented programmed temperature carbonization in a rotary kiln required for traditional asphalt coating, and simplifying the process flow.
[0056] The third stage: placing the kneaded graphite-asphalt mixture in a high-temperature furnace for carbonization treatment to carbonize the asphalt at a carbonization temperature of 1100-1250°C and a carbonization insulation time of 1-2 hours to remove volatile components in the asphalt and convert it into a more stable carbonaceous material. At the same time, the structural stability of the carbonaceous material that penetrates into the graphite pores and on the surface is enhanced, the performance of the recycled graphite is repaired, and the regenerated graphite negative electrode material has battery-grade performance, thereby improving the capacity and energy density of the lithium battery prepared as the negative electrode material in the future.
[0057] The graphite prepared by the above method has good structural integrity and good stability. The content of impurity elements is below 10ppm, the first lithium insertion capacity is above 380mAh / g, and the first lithium removal capacity is above 350mAh / g, which meets the standards of commercial battery-grade graphite materials.
[0058] The following is a further detailed description of the method for purifying, repairing and regenerating graphite from waste lithium batteries of the present application in conjunction with specific embodiments.
[0059] Embodiment 1:
[0060] This embodiment 1 adopts the following steps:
[0061] S1 After discharging the waste lithium battery at a constant potential of 0.50V, the disassembled and sorted negative electrode plates are placed in a high-frequency alternating magnetic field and plasma for treatment. The electromagnetic induction heating current is adjusted to 200A, the alternating magnetic field frequency is 20kHz, and the surface temperature of the metal copper current collector is controlled to be 350℃. At the same time, the plasma generator pulse power is adjusted to 20kW, the air flow rate is 10L / min, and the treatment time is controlled to 30s. Finally, the product is treated with ultrasonic vibration, passed through a 300-mesh sieve, and the sieve-under material is taken to obtain recycled graphite particles.
[0062] S2: 1 kg of graphite particles recovered from step S1 were dispersed in a 0.05 mol / L sulfuric acid solution in a stator-rotor high shear homogenizer with a rotation speed of 9000 rpm, the solid-liquid ratio was controlled to be 10 g / L, the leaching time was controlled to be 60 min, and then a graphite flotation inhibitor, sodium carboxymethyl cellulose, was added at a solid-liquid ratio of 0.3 g / L. After stirring for 10 min, an amorphous carbon capture agent, sodium dodecylbenzene sulfonate, was added at a solid-liquid ratio of 0.1 g / L. After further stirring for 10 min, a foaming agent, methyl isobutyl carbinol, was added at a solid-liquid ratio of 0.05 g / L. After reverse flotation for 10 min, amorphous carbon was removed.
[0063] S3 The product obtained in step S2 is mixed with a sulfuric acid solution having a concentration of 0.05 mol / L, with a solid-liquid ratio of 10 g / L, and then ethylenediaminetetraacetic acid is added, wherein 0.01 kg of ethylenediaminetetraacetic acid is added for every 1 kg of graphite treated, and stirred for 10 minutes to form an EDTA chelate, and then pickled with a 0.10 mol / L sulfuric acid solution to further leach out impurities such as metals and their oxides and inorganic non-metals in the SEI film to obtain a preliminarily decontaminated graphite substrate.
[0064] S4: Adjust the pH of the graphite substrate preliminarily decontaminated in step S3 to 2, add ferrous sulfate heptahydrate at 140 mg / L, stir for 10 min, and then add hydrogen peroxide dropwise at 85 mg / L in batches, controlling the dropwise addition rate to 2 mL / min·m 3 The reaction was further stirred for 30 minutes to fully oxidize and decompose the organic matter in the SEI film and recover the carbonate electrolyte remaining on the graphite surface. After filtration, deionized water washing, vacuum heating and drying, deeply purified graphite was obtained.
[0065] S5: The deeply purified graphite obtained in step S4 is put into a screw kneading device, and through segmented screw kneading, the extrusion pressure of the screw kneading device is controlled to 0.01MPa in the first stage, and degassed at room temperature for 2 minutes; in the second stage, asphalt is added at a mass ratio of 2.5wt%, and the mixture is kneaded with the deeply purified graphite put in the first stage, and the fluid asphalt is extruded and filled at 220℃ and 0.20MPa for 15 minutes; the graphite-asphalt mixture extruded from the screw kneading device is placed in a high-temperature furnace and carbonized at 1100℃ for 1h to obtain regenerated graphite with structural repair and surface carbon coating.
[0066] The structure and performance of this embodiment 1 are as follows:
[0067] Figure 2 The XRD diagram results show that the purified, repaired and regenerated graphite in Example 1 is a pure phase without any impurity phase.
[0068] Figure 3 The SEM image results show that the surface of the purified and repaired regenerated graphite in Example 1 has no impurities, cracks or holes.
[0069] Figure 4 The charge and discharge results show that the first cycle discharge specific capacity of the purified and repaired regenerated graphite in Example 1 at 0.1C charge and discharge is 384.5 mAh / g, the first cycle charge specific capacity is 355.3 mAh / g, and the first cycle coulomb efficiency is 92.41%. Its electrochemical performance has recovered to the average level of commercial graphite.
[0070] from Fig.17 It can be seen that the D50 of the purified and repaired regenerated graphite in Example 1 is 14.39 μm, and the D90 is 29.05 μm; the degree of graphitization is 97.87%, indicating that the graphite lattice damage has been repaired and the amorphous carbon has been removed; the iron, copper, aluminum and magnetic foreign matter are all less than 5 ppm, indicating that the graphite has been purified and the metal impurities have been removed; the fixed carbon content is 99.962% and the ash content is 0.038%, indicating that the graphite has been purified and the inorganic and organic impurities in the SEI film have been removed; the specific surface area is 2.155 m 2 / g, 5T compaction density is 1.91g / cm 3 , tap density is 1.15g / cm 3 , indicating that the pore defects in graphite have been repaired.
[0071] The above results show that the physical and chemical indicators of the purified and repaired regenerated graphite in Example 1 have met the standards of "Graphite Anode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0072] Embodiment 2:
[0073] This embodiment 2 adopts the following steps:
[0074] S1 After discharging the waste lithium battery at a constant potential of 0.50V, the disassembled and sorted negative electrode plates are placed in a high-frequency alternating magnetic field and plasma for treatment. The electromagnetic induction heating current is adjusted to 500A, the alternating magnetic field frequency is 30kHz, and the surface temperature of the metal copper current collector is controlled to 400℃. At the same time, the plasma generator pulse power is adjusted to 50kW, the air flow rate is 20L / min, and the treatment time is controlled to 60s. Finally, the product is treated with ultrasonic vibration, passed through a 200-mesh sieve, and the sieve-under material is taken to obtain recycled graphite particles.
[0075] S2: 1 kg of the recovered graphite particles obtained in step S1 were dispersed in a 0.10 mol / L sulfuric acid solution in a stator-rotor high shear homogenizer with a rotation speed of 12000 rpm, the solid-liquid ratio was controlled to be 50 g / L, the leaching time was controlled to be 120 min, and then a graphite flotation inhibitor, water glass, was added with a solid-liquid ratio of 1 g / L. After stirring for 20 min, an amorphous carbon capture agent, oleic acid, was added with a solid-liquid ratio of 0.2 g / L. After further stirring for 20 min, a frother, 2-ethylhexanol, was added with a solid-liquid ratio of 0.15 g / L. After reverse flotation for 15 min, amorphous carbon was removed.
[0076] S3 The product obtained in step S2 is mixed with a 0.1 mol / L sulfuric acid solution at a solid-liquid ratio of 50 g / L, and then ethylenediaminetetraacetic acid is added, wherein 0.05 kg of ethylenediaminetetraacetic acid is added for every 1 kg of graphite treated, and stirred for 20 minutes to form an EDTA chelate, and then pickled with a 0.10 mol / L sulfuric acid solution to further leach out impurities such as metals and their oxides and inorganic non-metals in the SEI film to obtain a preliminarily decontaminated graphite substrate.
[0077] S4: Adjust the pH of the graphite substrate preliminarily decontaminated in step S3 to 3, add ferrous sulfate heptahydrate at 560 mg / L, stir for 20 min, and then drip hydrogen peroxide at 340 mg / L in batches, controlling the dripping speed to 5 mL / min·m 3 The reaction was further stirred for 60 min to fully oxidize and decompose the organic matter in the SEI film and recover the carbonate electrolyte remaining on the graphite surface. After filtration, deionized water washing, vacuum heating and drying, deeply purified graphite was obtained.
[0078] S5 The deeply purified graphite obtained in step S4 is put into a screw kneading device. Through segmented screw kneading, the extrusion pressure of the screw kneading device is controlled to 0.05MPa in the first stage, and degassed at room temperature for 5 minutes. In the second stage, asphalt is added at a mass ratio of 8wt%, and the mixture is kneaded with the deeply purified graphite put in the first stage, and the fluid asphalt is extruded and filled at 280℃ and 0.30MPa for 25 minutes. The graphite-asphalt mixture extruded from the screw kneading device is then placed in a high-temperature furnace and carbonized at 1250℃ for 2h to obtain regenerated graphite with structural repair and surface carbon coating.
[0079] The structure and performance of this embodiment 2 are characterized as follows:
[0080] Figure 2 The XRD diagram results show that the purified, repaired and regenerated graphite in Example 2 is a pure phase without any impurity phase.
[0081] Figure 5 The SEM image results show that the surface of the purified, repaired and regenerated graphite in Example 2 has no impurities, cracks or holes.
[0082] Figure 6 The charge and discharge results show that the first cycle discharge specific capacity of the purified and repaired regenerated graphite in Example 2 at 0.1C charge and discharge is 384.2 mAh / g, the first cycle charge specific capacity is 353.2 mAh / g, and the first cycle coulomb efficiency is 91.93%. Its electrochemical performance has recovered to the average level of commercial graphite.
[0083] from Fig.17 It can be seen that the D50 of the purified and repaired regenerated graphite in Example 1 is 16.78 μm, and the D90 is 33.46 μm; the degree of graphitization is 97.82%, indicating that the graphite lattice damage has been repaired and the amorphous carbon has been removed; the iron, copper, aluminum and magnetic foreign matter are all less than 5 ppm, indicating that the graphite has been purified and the metal impurities have been removed; the fixed carbon content is 99.958% and the ash content is 0.042%, indicating that the graphite has been purified and the inorganic and organic impurities in the SEI film have been removed; the specific surface area is 2.132 m 2 / g, 5T compaction density is 1.92g / cm 3 , tap density is 1.14g / cm 3 , indicating that the pore defects in graphite have been repaired.
[0084] The above results indicate that the physical and chemical indicators of the purified and repaired regenerated graphite in Example 2 have met the standards of "Graphite Anode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0085] Embodiment 3:
[0086] This embodiment 3 adopts the following steps:
[0087] S1 After discharging the waste lithium battery at a constant potential of 0.50V, the disassembled and sorted negative electrode plates are placed in a high-frequency alternating magnetic field and plasma for treatment. The electromagnetic induction heating current is adjusted to 300A, the alternating magnetic field frequency is 25kHz, and the surface temperature of the metal copper current collector is controlled to 400℃. At the same time, the plasma generator pulse power is adjusted to 25kW, the air flow rate is 15L / min, and the treatment time is controlled to 40s. Finally, the product is treated with ultrasonic vibration, passed through a 150-mesh sieve, and the sieve-under material is taken to obtain recycled graphite particles.
[0088] S2: 1 kg of the recovered graphite particles obtained in step S1 were dispersed in a 0.1 mol / L sulfuric acid solution in a stator-rotor high shear homogenizer with a rotation speed of 10,000 rpm, and the solid-liquid ratio was controlled to be 30 g / L. The leaching time was controlled to be 90 min. Then, a graphite flotation inhibitor, sodium carboxymethyl cellulose, was added at a solid-liquid ratio of 0.6 g / L. After stirring for 15 min, an amorphous carbon capture agent, oleic acid, was added at a solid-liquid ratio of 0.15 g / L. After further stirring for 15 min, a frother, 2-ethylhexanol, was added at a solid-liquid ratio of 0.10 g / L. After reverse flotation for 15 min, amorphous carbon was removed.
[0089] S3 The product obtained in step S2 is mixed with a sulfuric acid solution with a concentration of 0.1 mol / L, with a solid-liquid ratio of 30 g / L, and then ethylenediaminetetraacetic acid is added, wherein 0.03 kg of ethylenediaminetetraacetic acid is added for every 1 kg of graphite treated, and stirred for 15 minutes to form an EDTA chelate, and then pickled with a 0.10 mol / L sulfuric acid solution to further leach out impurities such as metals and their oxides and inorganic non-metals in the SEI film to obtain a preliminarily decontaminated graphite substrate.
[0090] S4: Adjust the pH of the graphite substrate preliminarily decontaminated in step S3 to 3, add ferrous sulfate heptahydrate at 560 mg / L, stir for 20 min, and then drip hydrogen peroxide at 340 mg / L in batches, controlling the dripping speed to 3 mL / min·m 3 The reaction was further stirred for 40 minutes to fully oxidize and decompose the organic matter in the SEI film and recover the carbonate electrolyte remaining on the graphite surface. After filtration, deionized water washing, vacuum heating and drying, deeply purified graphite was obtained.
[0091] S5 The deeply purified graphite obtained in step S4 is put into a screw kneading device. Through segmented screw kneading, the extrusion pressure of the screw kneading device is controlled to 0.03MPa in the first stage, and degassed at room temperature for 5min. In the second stage, asphalt is added at a mass ratio of 5wt%, and the mixture is kneaded with the deeply purified graphite put in the first stage, and fluid asphalt is extruded and filled at 260℃ and 0.25MPa for 20min. The graphite-asphalt mixture extruded from the screw kneading device is then placed in a high-temperature furnace and carbonized at 1150℃ for 2h to obtain regenerated graphite with structural repair and surface carbon coating.
[0092] The structure and performance of this embodiment 3 are as follows:
[0093] Figure 2 The XRD diagram results show that the purified, repaired and regenerated graphite in Example 3 is a pure phase without any impurity phase.
[0094] Figure 7 The SEM image results show that the surface of the purified and repaired regenerated graphite in Example 3 has no impurities, cracks or holes.
[0095] Figure 8 The charge and discharge results show that the first cycle discharge specific capacity of the purified and repaired regenerated graphite in Example 3 at 0.1C charge and discharge is 384.9 mAh / g, the first cycle charge specific capacity is 352.1 mAh / g, and the first cycle coulomb efficiency is 91.48%. Its electrochemical performance has recovered to the average level of commercial graphite.
[0096] from Fig.17 It can be seen that the D50 of the purified and repaired regenerated graphite in Example 3 is 18.63 μm, and the D90 is 35.22 μm; the degree of graphitization is 97.83%, indicating that the graphite lattice damage has been repaired and the amorphous carbon has been removed; the iron, copper, aluminum and magnetic foreign matter are all less than 5 ppm, indicating that the graphite has been purified and the metal impurities have been removed; the fixed carbon content is 99.953% and the ash content is 0.047%, indicating that the graphite has been purified and the inorganic and organic impurities in the SEI film have been removed; the specific surface area is 2.129 m 2 / g, 5T compaction density is 1.92g / cm 3 , tap density is 1.18g / cm 3 , indicating that the pore defects in graphite have been repaired.
[0097] The above results show that the physical and chemical indicators of the purified and repaired regenerated graphite in Example 3 have met the standards of "Graphite Anode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0098] Comparative Example 1:
[0099] This comparative example 1 adopts the following steps:
[0100] S1 After the waste lithium battery is discharged at a constant potential of 0.50V, it is placed in a nitrogen atmosphere and heated to 500℃ and kept at a constant temperature for 3h to fully pyrolyze and carbonize the binder to obtain a preliminarily treated negative electrode sheet. It is then placed in water and treated at a 400W ultrasonic power for 20min to separate the coating and copper current collector on the negative electrode sheet. After passing through a 200-mesh sieve, the sieve-under material is taken to obtain preliminarily separated graphite particles.
[0101] S2 The graphite particles preliminarily separated in step S1 are placed in a H2SO4 solution with a concentration of 1.2 mol / L, heated in a water bath at 45°C under a solid-liquid ratio of 10 g / L, and leached for 2 h with a paddle stirring at 3000 rpm to obtain preliminarily decontaminated graphite.
[0102] The remaining steps S3 to S5 are the same as those in Example 1.
[0103] The structure and performance of this comparative example 1 are as follows:
[0104] Figure 2 The XRD pattern results show that the graphite obtained in Comparative Example 1 presents a broad diffraction peak bulge at about 20-26° (2 Theta), without other impurity phases, and the obtained graphite contains a small amount of amorphous carbon.
[0105] Fig. 9 The SEM results show that the graphite surface obtained in Comparative Example 1 contains a large number of carbon black spherical small particle aggregates and amorphous carbon particles (impurities are obvious on the graphite surface), but there are no cracks or holes on the surface. Therefore, the results of Comparative Examples 1 to 3 show that the application uses high-frequency alternating magnetic field and atmospheric plasma in combination with stator-rotor high shear homogenization and reverse flotation methods to effectively remove amorphous carbon produced by high-temperature pyrolysis of organic binders on the graphite surface, especially carbon black conductive agent aggregates.
[0106] Fig.10 The charge and discharge results show that the first cycle discharge capacity of the graphite obtained in Comparative Example 1 is 391.0 mAh / g, the first cycle charge capacity is 341.7 mAh / g, and the first cycle coulomb efficiency is 87.41% in 0.1C charge and discharge. It can be seen that due to the residual amorphous carbon in the graphite of Comparative Example 1, the first cycle charge capacity and coulomb efficiency are low.
[0107] from Fig.18It can be seen that the D50 of the graphite obtained in this comparative example 1 is 15.24 μm, and the D90 is 31.26 μm; the degree of graphitization is 96.23%, indicating that some amorphous carbon remains in the graphite; iron, copper, aluminum and magnetic foreign matter are all less than 5 ppm, but the copper content is 0.873 ppm, which is higher than the copper content in Examples 1 to 3, mainly because the high-temperature carbonization pyrolysis stripping at 500 ° C causes the copper collector to be brittle and difficult to separate; the fixed carbon content is 99.879% and the ash content is 0.121%, which is much higher than the ash content in Examples 1 to 3, mainly due to the residual trace copper. At the same time, there is no lamellar residue structure on the surface, indicating that the inorganic impurities and organic impurities in the SEI film have been removed; the specific surface area is 3.152 m 2 / g, 5T compaction density is 1.87g / cm 3 , tap density is 1.09g / cm 3 , which is lower than the compaction and tap density in Examples 1 to 3, mainly because the amorphous carbon in the graphite is not completely removed; in addition, the pore defects in the graphite have been repaired.
[0108] The above results show that the first-cycle coulomb efficiency in the electrochemical performance of Comparative Example 1 is less than 91%, which does not meet the standard of "Graphite Anode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0109] Comparative Example 2:
[0110] This comparative example 2 adopts the following steps:
[0111] S1 is the same as Comparative Example 1.
[0112] S2: 1 kg of graphite particles recovered from step S1 were dispersed in 0.1 mol / L sulfuric acid solution with stirring, and the solid-liquid ratio was controlled to be 30 g / L. The leaching time was controlled to be 90 min. Then, a graphite flotation inhibitor, sodium carboxymethyl cellulose, was added with a solid-liquid ratio of 0.6 g / L. After stirring for 15 min, an amorphous carbon capture agent, oleic acid, was added with a solid-liquid ratio of 0.15 g / L. After further stirring for 15 min, a frother, 2-ethylhexanol, was added with a solid-liquid ratio of 0.10 g / L. After reverse flotation for 15 min, amorphous carbon was removed.
[0113] S3 The pH value of the product after reverse flotation and removal of amorphous carbon was adjusted to 3, and ferrous sulfate heptahydrate was added at 560 mg / L. The mixture was further stirred for 20 min, and then hydrogen peroxide was added dropwise at 340 mg / L in batches. The dropping speed was controlled at 3 mL / min·m 3 The reaction was further stirred for 40 minutes to fully oxidize and decompose the organic matter in the SEI film and recover the carbonate electrolyte remaining on the graphite surface. After filtration, washing and drying, deeply purified graphite was obtained.
[0114] Step S4 is the same as step S5 in Example 1.
[0115] The structure and performance of this comparative example 2 are as follows:
[0116] Figure 2 The XRD results show that the graphite obtained in Comparative Example 2 presents a broad diffraction peak bulge at about 20-26° (2 Theta), with no other impurity phases, and the obtained graphite contains only a trace amount of amorphous metals or their compounds.
[0117] Fig.11 The SEM results show that since the step 1 of comparative example 2 does not use a stator-rotor high shear homogenizer for dispersion, the graphite surface obtained contains a small amount of carbon black spherical small particle aggregates, but there are no cracks or holes on the surface. It can be seen that the stator-rotor high shear homogenizer dispersion used in this application can effectively remove carbon black conductive agent aggregates.
[0118] Fig.12 The charge and discharge results show that the first cycle discharge capacity of the graphite obtained in Comparative Example 2 is 349.7 mAh / g, the first cycle charge capacity is 297.1 mAh / g, and the first cycle coulomb efficiency is 84.96% in 0.1C charge and discharge. Since Comparative Example 2 does not undergo chelation treatment, trace amounts of amorphous metals or their compounds remain in the graphite, resulting in reduced first cycle charge and discharge capacity and coulomb efficiency.
[0119] from Fig.18 It can be seen that the D50 of the graphite obtained in this comparative example 2 is 17.16 μm, and the D90 is 34.94 μm; the degree of graphitization is 97.68%, indicating that the damage to the graphite lattice has been repaired and most of the amorphous carbon has been removed; iron, copper, aluminum and magnetic foreign matter are all greater than 5 ppm, of which iron is 136.329 ppm, copper is 912.184 ppm, aluminum is 79.256, and magnetic foreign matter is 25.584, which is greatly improved compared with the metal content in Examples 1 to 3, mainly due to the lack of EDTA chelation to remove metal impurity ions or amorphous metals or their compounds in the graphite; the fixed carbon content is 99.627%, and the ash content is 0.273%, which is higher than the ash content in Comparative Example 1, mainly due to the lack of EDTA chelation to remove metal impurity ions or amorphous metals or their compounds in the graphite, and at the same time, the surface graphite has been purified, and the inorganic impurities and organic impurities in the SEI film have been removed; the specific surface area is 2.273 m 2 / g, 5T compaction density is 1.90g / cm 3 , tap density is 1.13g / cm 3 , the pore defects in the surface graphite have been repaired.
[0120] The above results show that the trace metal element iron content of Comparative Example 2 is greater than 100 ppm, the copper and aluminum contents are greater than 5 ppm, the magnetic foreign matter is greater than 0.5 ppm, the fixed carbon content is less than 99.70%, and the first-circuit coulomb efficiency in electrochemical performance is less than 91%, which does not meet the "Graphite Negative Electrode Materials for Lithium-ion Batteries" (GB / T 24533-2019) standard.
[0121] Comparative Example 3:
[0122] This comparative example 3 adopts the following steps:
[0123] S1~S3 are the same as in Example 1.
[0124] S4: The graphite obtained in step S3 with preliminary impurity removal is put into a screw kneading device. Through segmented screw kneading, the extrusion pressure of the screw kneading device is controlled to 0.03MPa in the first stage, and degassed at room temperature for 5 minutes. In the second stage, asphalt is added at a mass ratio of 5wt%, and the mixture is kneaded with the deeply purified graphite put in the first stage, and the fluid asphalt is extruded and filled at 260℃ and 0.25MPa for 20 minutes. The graphite-asphalt mixture extruded from the screw kneading device is then placed in a high-temperature furnace and carbonized at 1150℃ for 2h to obtain regenerated graphite with structural repair and surface carbon coating.
[0125] The structure and performance of this comparative example 3 are as follows:
[0126] Figure 2 The XRD diagram results show that the graphite obtained in this comparative example 3 is a pure phase without any impurity phase.
[0127] Fig.13 The SEM results show that the graphite surface obtained in Comparative Example 3 has no cracks or holes. Since no oxidation purification step is used, there are lamellar residual carbonate electrolyte residual derivatives on the graphite surface. Comparing the results of Examples 1 to 3 above, it is shown that the oxidation purification step used in this application can effectively remove inorganic and organic impurities in the SEI film.
[0128] Fig.14 The charge and discharge results show that the first cycle discharge capacity of the graphite obtained in this comparative example 2 is 380.3mAh / g, the first cycle charge capacity is 343.2mAh / g, and the first cycle coulomb efficiency is 90.24% in 0.1C charge and discharge. Comparing the results of the above examples 1 to 3, it is shown that the trace amount of inorganic and organic impurities in the SEI film remaining in the graphite will lead to a decrease in the first cycle charge capacity, electric capacity and coulomb efficiency.
[0129] from Fig.18It can be seen that the D50 of the graphite obtained in this comparative example 3 is 18.40 μm, and the D90 is 34.46 μm; the degree of graphitization is 97.84%, indicating that the graphite lattice damage has been repaired; the iron, copper, aluminum and magnetic foreign matter are all less than 5 ppm, indicating that the graphite has been purified and the metal impurities have been removed; the fixed carbon content is 99.889%, and the ash content is 0.111%, which is much higher than the ash content in Examples 1 to 3, mainly due to inorganic and organic impurities in the SEI film; the specific surface area is 2.161 m 2 / g, 5T compaction density is 1.92g / cm 3 , tap density is 1.14g / cm 3 , the pore defects in the surface graphite have been repaired.
[0130] The above results show that the first-cycle coulomb efficiency of the electrochemical performance of Comparative Example 3 is less than 91%, which does not meet the standard of "Graphite Anode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0131] Comparative Example 4:
[0132] This comparative example 4 adopts the following steps:
[0133] S1~S4 are the same as in Example 1.
[0134] S5: adding asphalt at a mass ratio of 5wt% to the deeply purified graphite obtained in step S4, placing the mixture in a roller kiln, heating the mixture to 260°C at a rate of 5°C / min in a high-purity nitrogen atmosphere, keeping the temperature for 1h, then heating the mixture to 1150°C at the same rate, keeping the temperature for 2h, to obtain carbon-coated regenerated graphite.
[0135] The structure and performance of this comparative example 4 are as follows:
[0136] Figure 2 The XRD diagram results show that the graphite obtained in this comparative example 4 is a pure phase without any impurity phase.
[0137] Fig.15 The SEM results show that the graphite surface obtained in Comparative Example 4 has no impurities, but has cracks and holes. Comparative Examples 1 to 3 show that the segmented screw pressure infiltration coating used in this application can effectively allow asphalt to fill the surface defects and internal holes of graphite.
[0138] Fig.16 The charge and discharge results show that the first cycle discharge capacity of the graphite obtained in Comparative Example 4 is 392.1 mAh / g, the first cycle charge capacity is 351.7 mAh / g, and the first cycle coulomb efficiency is 89.70% in 0.1C charge and discharge. It can be seen that when there are cracks on the surface of graphite and holes inside, the first cycle coulomb efficiency will be reduced.
[0139] from Fig.18 It can be seen that the D50 of the graphite obtained in this comparative example 4 is 18.34 μm, and the D90 is 35.65 μm; the degree of graphitization is 97.70%, indicating that the graphite lattice damage has been partially repaired; the iron, copper, aluminum and magnetic foreign matter are all less than 5 ppm, indicating that the metal impurities have been removed; the fixed carbon content is 99.942%, and the ash content is 0.058%, indicating that the graphite has been purified, and the inorganic and organic impurities in the SEI film have been removed; the specific surface area is 4.867 m 2 / g, 5T compaction density is 1.73g / cm 3 , tap density is 0.98g / cm 3 , the pore defects in the surface graphite are not completely repaired.
[0140] The above results show that the specific surface area of comparative example 4 is greater than 4.5 m 2 / g, tap density <1.00g / cm 3 , the first-cycle coulomb efficiency in electrochemical performance is less than 91%, which does not meet the standard of "Graphite Negative Electrode Materials for Lithium-ion Batteries" (GB / T 24533-2019).
[0141] The present application also provides a graphite negative electrode plate, which is prepared by using the recycled waste lithium battery graphite using the structurally repaired and surface carbon-coated regenerated graphite obtained above as the negative electrode active material. When it is used to prepare a lithium-ion battery, the first-cycle coulomb efficiency is greater than 91.4%, which reliably guarantees the electrochemical performance of the lithium-ion battery and can meet the requirements of commercial energy storage lithium batteries.
[0142] The present application also provides a lithium-ion battery, the preparation of which includes the above-mentioned graphite negative electrode plate, which solves the problem of recycling negative electrode materials of waste lithium batteries and reduces the manufacturing cost of lithium-ion batteries.
[0143] The above-mentioned embodiments of the present application are only part of the preferred embodiments of the present application and cannot be used to limit the present application. Without departing from the essence of the present application, any modifications, equivalent substitutions and improvements made by technical personnel in this field are within the scope of protection of the present application.
Claims
1. A method for purifying, repairing and regenerating graphite from waste lithium batteries, characterized in that: The steps include: S1. Placing the negative electrode of the waste lithium battery in a high-frequency alternating magnetic field, controlling the electromagnetic induction heating current to be within the range of 200A to 500A, the alternating magnetic field frequency to be 20 to 30kHz, the surface temperature of the copper current collector in the negative electrode of the waste lithium battery to be 350 to 400°C, and treating the negative electrode of the waste lithium battery with a plasma generator, the pulse power of the plasma generator to be 20 to 50kW, so that cracks are formed in the coating between the graphite in the negative electrode of the waste lithium battery and the copper current collector and the interface between the coating and the copper current collector is dislocated, and then the graphite is peeled off from the copper current collector by ultrasonic vibration, and the graphite particles are recovered after sieving; S2. dispersing the recovered graphite particles in a dilute acid solution, adding a graphite flotation inhibitor, stirring, adding an amorphous carbon capture agent, stirring, and then adding a frother, and after reverse flotation, removing the amorphous carbon; S3: mixing the product obtained in step S2 with a dilute acid solution, then adding a chelating agent, stirring to form a chelate, and then washing with a dilute acid solution to leach out metals, oxides and inorganic substances in the SEI film in the product, thereby obtaining a preliminarily impurity-removed graphite substrate; S4: adjusting the pH value of the preliminarily impurity-removed graphite substrate obtained in step S3 to 2-3, adding ferrous sulfate heptahydrate, adding hydrogen peroxide dropwise after sufficient stirring, and then stirring to react to oxidize and decompose organic matter in the SEI film and the carbonate electrolyte remaining on the surface of the graphite particles, and filtering, washing, and drying to obtain deeply purified graphite; S5: adding high-temperature petroleum asphalt to the deeply purified graphite obtained in step S4, kneading it through a screw kneading device and then carbonizing it at high temperature to obtain regenerated graphite with repaired structure and carbon coating on the surface.
2. The method for purifying, repairing and regenerating graphite from waste lithium batteries according to claim 1, characterized in that: In the step S1, the air flow rate in the high-frequency alternating magnetic field is controlled at 10 to 20 L / min, and the processing time is 30 to 60 seconds.
3. The method for purifying, repairing and regenerating graphite from waste lithium batteries according to claim 1, characterized in that: In the step S2, when the graphite particles are dispersed in the dilute acid solution, the solid-liquid ratio of the graphite particles to the dilute acid solution is 10 to 50 g / L, and the graphite particles are dispersed in the dilute acid solution by a stator-rotor high shear homogenizer, the shear speed is 9000 to 12000 rpm, and the time is 60 to 120 min.
4. The method for purifying, repairing and regenerating graphite from waste lithium batteries according to claim 1, characterized in that: In the step S2 and the step S3, the dilute acid is sulfuric acid, and the concentration of the sulfuric acid solution is 0.05-0.10 mol / L.
5. The method for purifying, repairing and regenerating graphite from waste lithium batteries according to any one of claims 1, 3 or 4, characterized in that: In the step S2, the graphite flotation depressant is selected from at least one of sodium carboxymethyl cellulose or water glass, the solid-liquid ratio of the graphite particles to the graphite flotation depressant is 0.3-1 g / L, and the graphite flotation depressant is added and stirred for 10-20 minutes; the amorphous carbon capture agent is selected from at least one of sodium dodecylbenzene sulfonate or oleic acid, the solid-liquid ratio of the graphite particles to the amorphous carbon capture agent is 0.1-0.2 g / L, and the amorphous carbon capture agent is added and stirred for 10-20 minutes; the foaming agent is selected from at least one of methyl isobutyl carbinol or 2-ethylhexanol, the solid-liquid ratio of the graphite particles to the foaming agent is 0.05-0.15 g / L; and the reverse flotation time is 10-15 minutes.
6. The method for purifying, repairing and regenerating graphite from waste lithium batteries as claimed in claim 4, characterized in that: In the step S3, the solid-liquid ratio of the product obtained in the step S2 to the sulfuric acid solution is 10 to 50 g / L; the chelating agent is ethylenediaminetetraacetic acid, the mass ratio of the graphite particles to the ethylenediaminetetraacetic acid is 1:0.01 to 0.05, and the stirring time after adding the ethylenediaminetetraacetic acid is 10 to 20 minutes.
7. The method for purifying, repairing and regenerating graphite from waste lithium batteries according to claim 1, characterized in that: In the step S4, 140-560 mg / L of ferrous sulfate heptahydrate is added, stirred for 10-20 min, and then 85-340 mg / L of hydrogen peroxide is added dropwise in batches at a rate of 2-5 mL / min·m 3 , and further stir for 30 to 60 minutes.
8. The method for purifying, repairing and regenerating graphite from waste lithium batteries as claimed in claim 1, characterized in that: The S5 step is divided into three stages. In the first stage, the deeply purified graphite is put into a screw kneading device, the screw extrusion pressure is controlled, and degassing is performed at room temperature. In the second stage, asphalt with a mass ratio of 2.5 to 8 wt% is added to the deeply purified graphite, and the deeply purified graphite and the asphalt are kneaded at a temperature higher than the softening point of solid asphalt. In the third stage, the kneaded graphite-asphalt mixture is carbonized.
9. The method for purifying, repairing and regenerating graphite from waste lithium batteries as claimed in claim 8, characterized in that: In the S5 step, the screw extrusion pressure of the screw kneading equipment in the first section is 0.01-0.05MPa, and the room temperature degassing time is 2-5min. The screw extrusion pressure of the screw kneading equipment in the second section is 0.20-0.30MPa, the solid asphalt softening point temperature is 220-280°C, and the kneading time is 5-10min. The third section is to place the kneaded graphite-asphalt mixture in a high-temperature furnace to carbonize the asphalt, the carbonization temperature is 1100-1250°C, and the carbonization insulation time is 1-2h.
10. A graphite negative electrode plate, characterized in that: The regenerated graphite obtained by the method according to any one of claims 1 to 9 is used as the negative electrode active material for preparation.
11. A lithium ion battery, characterized in that: Comprising the graphite negative electrode sheet as claimed in claim 10.
Citation Information
Patent Citations
Regeneration method of lithium ion battery negative electrode graphite
CN111285366A
Method for recycling negative electrode graphite of lithium ion battery
CN114597533A
Method for recovering graphite from waste lithium ion battery black powder
CN118993062A
Method for plasma-assisted stripping of pole piece active material and current collector of lithium ion battery
CN119581718A
Method for preparing battery-grade graphite by using mixed waste of positive and negative electrode materials of failed lithium-ion battery as raw material
WO2023227032A1
Cited By
Method for deeply purifying, repairing and regenerating graphite waste residues of waste lithium ion batteries
CN119315160A